Erythropoietin, a novel repurposed drug: An innovative treatment for wound healing in patients with diabetes mellitus. Issue 1 (13th December 2013) - Hamed, Saher; Bennett, Charles L.; Demiot, Claire; Ullmann, Yehuda; Teot, Luc; Desmoulière, Alexis
Abstract Developing a new drug is expensive: the cost of going from bench to bedside is about US1 billion. Therefore, the repurposing of an approved drug is potentially rewarding because it expands the drug's existing therapeutic profile and preempts additional development costs. As the safety profile of a repurposed drug is already well known, any new investigations could then focus on its efficacy and other therapeutic benefits. Recombinant erythropoietin (EPO) is a potential candidate for repurposing because the results of numerous studies have shown that systemic and topical EPO is therapeutically beneficial when it is administered to healthy and diabetic animals with acute and chronic skin wounds and burns. Moreover, the molecular mechanisms of EPO's actions have been elucidated: EPO acts on those nonhematopoietic cells which are involved in the innate immune response where it promotes cellular proliferation and differentiation, exerts its cytoprotective actions, and inhibits apoptosis. In this review, the mechanism of EPO's action in skin wound healing is reviewed, and its potential for treating acute and chronic skin wounds and stimulating tissue regeneration in diabetic patients is discussed.